The catalytic combustion for natural gas - Wan Abu Bakar, Wan Azelee; Buang, Nor Aziah (Universiti Teknologi Malaysia, 2001)
Noble metals such as Pt, Rh and Pd have been widely used as catalyst for the catalytic combustion(oxidation) of methane. They can be used either with or without a support but supported catalysts are favored for the combustion. The disadvantages of noble metals in catalytic combustion application are i) limited supply, ii) high price, iii) high volatility and iv) ease of combustion. As such a viable alternative material should be invented which can overcome all the weakness possess by the noble metals and which can give much better performance of catalytic combustion of methane. In this research all possible catalyst based on metal oxides were prepared using various preparation techniques. The catalytic activity was determined using fixed-bed micro reactor whereby the temperature for 100 % conversion of methane was determined. The main selection of the catalysts used are high physical and chemical stability, cheap, high availability and local mineral resources. The combustion of methane over various catalysts that has been studied were metal oxides or mixed metal oxides such as Mn/SnO2, Sn/Ln2O3 (Ln = La, Pr, Nd, Sm, Gd), Sn/ZrO2, Cu/SnO2, Sn/CeO2 and Cu/ZrO2. The catalytic combustion of the prepared catalysts in this research, in general, are accomplished at high temperature i.e. above 500oC. The XRD analysis showed that the prepared catalysts have some degree of amorphous properties which might serve as the active sites. The XPS results showed that the surface of the catalysts are enriched with oxygen and the atoms distribution are more homogeneous upon ageing, with a fair amount of dopants on the surface. The TG/DTG analysis showed the complete elimination of water and residual species at 300 oC for all catalysts. DTA analysis agrees with TG/DTG whereby the complete removal of surface water and foreign species occurred below 300 oC. FTIR analysis showed that the existence of hydroxyl group occurred at 400 oC which indicated that there is a need for a certain amount of water for good catalytic reaction. Nitrogen adsorption analysis showed that the catalyst consists of a mixture of micro- and mesopores with non-uniform slit shaped pores. Different calcination temperatures will result in a different shape of pores. The SEM micrograph on the best catalyst showed that the catalyst has evenly distributed particle size at the range of 11-32 Âµm.